The The Influence of Accounting Information System Service Quality and the Use of Fintech Gateway Payments on the Performance of MSMEs in Medan Marelan District: Pengaruh Kualitas Layanan Sistem Informasi Akuntansi dan Penggunaan Fintech Gateway Payment Terhadap Kinerja Usaha Umkm di Kecamatan Medan Marelan - Cindy Stefanny; Putri wahyuni (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2025)
In the digital era, the adoption of technology and accounting information systems is crucial for improving business performance, including in the MSME sector. This study analyzes the effect of accounting information system service quality and the use of Fintech Gateway Payments on the performance of MSMEs in Medan Marelan District. The population consisted of 284 MSMEs in 2025, with 108 samples selected through purposive sampling of businesses using accounting information system and Fintech services. Data were collected using Likert-scale questionnaires and analyzed with multiple linear regression through SPSS. The findings show that AIS service quality has a significant partial effect on MSME performance, and Fintech Gateway Payments also significantly influence performance. Simultaneously, both variables have a significant combined effect, explaining 54.4% of the variance in MSME performance. These results highlight the role of AIS and Fintech in enhancing efficiency, competitiveness, and sustainability in MSMEs.